Cord Blood Albumin as a Predictor of Significant Hyperbilirubinemia in Term and Preterm Neonates - Anurag Singh Chandel; Ravindra Chittal (Asian Journal of Clinical Pediatrics and Neonatology, 2020)
Background: Jaundice is the most common condition requiring medical attention and readmission. As neonates are discharged within 48 hours of birth, close follow up is very important to look for jaundice. In developing countries, follow up visits are difficult. Therefore, it is important to identify at risk neonates before discharge. This study helps in identifying neonates at risk for hyperbilirubinemia. This study includes both healthy pre-term and full term neonates.Aim & Objective:To find correlation between cord blood albumin level with serum bilirubin level in healthy term and preterm neonates and correlation between maternal serum albumin level with cord blood albumin.Subject and Method:This study included 106 neonates (full-term and pre-term) born in Lilavati Hospital, Mumbai during period of March to December 2017. Result:Out of 106 neonates, 42(39.6%) developed significant hyperbilirubinemia. 17 (58.6%) neonates with cord blood albumin below 2.8 g/dl required phototherapy against 24 (50%) with cord blood albumin between 2.8-3.3 g/dl. In this study, 11 (73.3%) out of 15 pre-term and 6 (42.9%) of 14 full-term neonates with cord blood albumin below 2.8 g/dl developed significant hyperbilirubinemia and required phototherapy. A significant association wasobserved between maternal and cord blood albumin level. Conclusion:Significant association observed between cord blood albuminand tendencies of significant hyperbilirubinemia. So, cord blood albumin can be used as a surrogate marker for screening newborns for development of significant hyperbilirubinemia